Challenges of Fisherwomen of Loktak Lake, Manipur - Devi, Sagolshem Sophia; Moirangleima, Khundrakpam (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
An attempt was done in the Bishnupur district of Manipur to evaluate the issues faced by the women who worked as fishermen in the three villages of Thanga, Ithing, and Phubala as well as one island (Karang). To gather the data for this study, primary sources were used. With 350 respondents, at a confidence level of 95%, and a margin of error of 3%, semi-structured interviews were performed in the academic year 2019–2020. As a result, 90 percent of the sampled respondents work in the fishing industry, including fishing, fish selling, fish drying, and fish preservation, and 53 percent have over 10 years of experience in this field. They are also literate (80 percent). However, they encountered numerous difficulties, including using outdated fishing methods, a decline in fish yield due to an increase in the number of fisherwomen, a shortage of transportation, a lack of storage, etc. Implementing appropriate government actions, policies, and programmes is necessary for the fishing sector as well living conditions of the people.